The relationship between the habit of brushing teeth before sleeping at night and the caries status of children aged 9-12 years: relationship between the habit of brushing teeth before sleeping at night and the caries status of children aged 9-12 years - Sitti Fadhilla Oemar M; Sari Aldilawati; Azzahra Anindya (Makassar Dental Journal, 2024)
The habit of brushing teeth is very helpful in cleaning food residue on the teeth. Primary school age is the right time to provide a solid foundation for quality human beings, because health is the main factor to determine their quality. This study aimed to deter-mine the relationship between the habit of brushing teeth before going to bed at night on the caries status of children aged 9-12 years. Analytical observational study using cross sectional design. Spearman statistical test was used in this study involving 60 samples. Based on the Spearman Rho correlation test, the p-value was 0.01 or p<0.05. The correlation coefficient shows a value of 0.722 which means the correlation is strong. This means that there is a significant relationship between the habit of brushing teeth at night and the caries status of children aged 9-12 years at SDN 57 Pare-Pare. It is concluded that the habit of brushing teeth before going to bed at night affects the caries status of children aged 9-12 years.